Змістовні складові програми й основні техніки соціально-психологічного тренінгу соціального інтелекту поліцейського - Харченко, С. В.; Kharchenko, S. V.; Svitlana Kharchenko (Право і безпека. – 2017. – № 4 (67). – С.211-216, 2017)
Охарактеризовано складові соціально-психологічного тренінгу соціального інтелекту поліцейських. Використання описаних технік спрямовано на розвиток: адекватного сприйняття емоційної та вербальної експресії партнерів у спілкуванні; розуміння мотивів співрозмовників; вміння передбачити розвиток комунікативної ситуації; вміння донести власну думку до різних за індивідуальними властивостями осіб. Такі техніки можуть бути застосовані в процесі підготовки курсантів у ВНЗ зі специфічними умовами навчання або для післядипломної освіти поліцейських різних підрозділів.

It has been noted that social mental capacity provides obtaining and efficient processing of maximum information about the behavior of people and groups. Improvement of abilities of social mental capacity of the person takes place with the help of specially organized training. Suggested by the author techniques of social and psychological training of social mental capacity of police officers are mostly aimed at the development of such abilities: to adequately perceive the emotional reactions of partners within professional communication; correctly understand the motives of the interlocutors; to anticipate the development of a communicative situation; to adequately perceive the verbal expression of interlocutors; correctly understand own influence on the deployment of the situation of interaction; the ability to express oneself clearly for the various individual characteristics of individuals. It has been stressed that in the process of training it is necessary to strive for the participants to have a correct, integral, close to the intuitive understanding of emotions, states, motives in the process of communication, etc. Regarding police officers with experience, we must pay attention to reducing stereotypes in the processes of social phenomena cognition. It has been noted that the program of social and psychological training of social mental capacity often includes mini-lectures, individual work exercises, activities in small groups (4–5 people) and the activity of the whole group. The author has presented techniques of social and psychological training of social mental capacity that can be used by psychologist trainers in the process of professional training of cadets in higher educational establishments with specific training conditions or during the advanced training of police officers from different divisions. Techniques of social and psychological training of social mental capacity were selected by the author and tested in the process of teaching at Kharkiv National University of Internal Affairs. From the proposed techniques, the psychologist trainer can compile a scenario of social and psychological training of the abilities of social mental capacity for participants with certain differences within the content of professional activity.

Охарактеризованы компоненты социально-психологического тренинга социального интеллекта полицейских. Использование описанных техник направлено на развитие: адекватного восприятия эмоциональной и вербальной экспрессии партнёров по общению; понимания мотивов собеседников; умения предвидеть развитие коммуникативной ситуации; умения доносить свою мысль до различных по индивидуальным свойствам людей. Такие техники могут быть применены в процессе подготовки курсантов в вузах со специфическими условиями обучения или для последипломного образования полицейских разных подразделений.
Content components of the program and main techniques of social and psychological training of a police officer’s social mental capacity
Содержательные компоненты и основные техники социально-психологического тренинга социального интеллекта полицейского
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; соціальний інтелект; Юридична психологія. Legal psychology. Юридическая психология; ділове спілкування; соціально-психологічний тренінг; професійна підготовка; поліцейський; social mental capacity; professional communication; social and psychological training; professional training; police officers; социальный интеллект; деловое общение; социально-психологический тренинг; профессиональная подготовка; полицейский